Perkembangan Paradigma Epistemologi dalam Filsafat Islam - Fathul Mufid (Ulumuna, 2013)
Based on historical reports, Islamic epistemology paradigm has evolved from time to time bringing different schools each other. This paper aims at revealing such differences. Methods employed are philosophical Literary Review where compiled data are analyzed inductively to formulate theoretical constructions. Research findings reveal that peripatetic philosophers highlight their mind as a dominant tool to gain knowledge using demonstrative method (burhānī).Whilst illuminative philosophers, ‘irfāniyyīn, and Sufis believe that knowledge can only be derived from mystical intuition after purification of the heart (qalb) trough practices (riyāḍah). Different schools such as ones held by Mulla Sadra and Abed al-Jabiri are based on those distinctive principles.